2016
DOI: 10.1038/srep36898
|View full text |Cite
|
Sign up to set email alerts
|

Competition Between Resonant Plasmonic Coupling and Electrostatic Interaction in Reduced Graphene Oxide Quantum Dots

Abstract: The light emission from reduced graphene oxide quantum dots (rGO-QDs) exhibit a significant enhancement in photoluminescence (PL) due to localized surface plasmon (LSP) interactions. Silver and gold nanoparticles (NPs) coupled to rGO nanoparticles exhibit the effect of resonant LSP coupling on the emission processes. Enhancement of the radiative recombination rate in the presence of Ag-NPs induced LSP tuned to the emission energy results in a four-fold increase in PL intensity. The localized field due to the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 35 publications
(54 reference statements)
1
10
0
Order By: Relevance
“…3(a) ) shows a peak at 284.6 eV, corresponding to sp 2 carbon framework in a conjugated honey-comb. Three components centered at 286.4 eV, 287.1 eV and 288.7 eV are related to C-OH, C-O-C (epoxy and alkoxy), and C=O groups, respectively, which are in good agreement with the previous reports 21 , 22 . For RGO (Fig.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…3(a) ) shows a peak at 284.6 eV, corresponding to sp 2 carbon framework in a conjugated honey-comb. Three components centered at 286.4 eV, 287.1 eV and 288.7 eV are related to C-OH, C-O-C (epoxy and alkoxy), and C=O groups, respectively, which are in good agreement with the previous reports 21 , 22 . For RGO (Fig.…”
Section: Resultssupporting
confidence: 91%
“…The deconvolution of each C 1s spectrum has been summarized in Table 1 . According to XPS spectrum, it is found that the C/O ratio is 2.96 for GO, indicating a high oxygen atomic percentage in the as-prepared GO though it is a high-bound estimate for the real value 19 , 21 . The C 1s core level XPS of GO (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, in the presence of the GaNPs, the attraction of the electron and hole leads to the electrostatic effect which results in an image charge induced Stark effect. 29,31 As the image charge results in a Coulomb attraction of the carriers, the force of the attraction depends on the location of the charge carriers with respect to its distance from the metal nanoparticles. It results in a modification of the alignment of the conduction band and valence band line-up with respect to the spatial distance along the z-direction (growth direction) due to its difference in the distance from the Ga nanodroplet surface.…”
Section: Nanoscale Papermentioning
confidence: 99%
“…A higher concentration of metal nanoparticles around a plasmonic emitter can be detrimental to the plasmonically enhanced light emission process as the plasmon frequency can be detuned away from the light emission energy. 31 Moreover, single-species metal nanoparticle plasmon systems have one specific bandwidth of plasmon frequency. The presence of an additional plasmon species to a plasmonic light emitter can enable the stimulation of hot carrier generation and photoexcited carrier density modulation.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the HOMO energy level presented in the Fig. 6 corresponds to the average HOMO energy for all structures obtained from the MD simulations at temperature of 300 K. The values of work function of the rGO/AgNPs were obtained from the literature, in which a large range of values are related, depending of the Ag nanoparticles size and concentration [43][44][45][46][47].…”
Section: Theoretical Analysismentioning
confidence: 99%